Analyzing influential factors determining cropland lease contract choice between cash rent and cropshare - Tyree, Trevor Jene (Kansas State University, 2019)
Cropland tenants and landowners must agree on a type of contract when entering a lease. Historically, the two most popular types of contracts are cash rent and cropshare. What variables cause tenants and landowners to choose one type of contract over the other? Is it simply a random decision? Or are there tangible, identifiable, quantifiable factors that play a role? This thesis attempts to determine the most influential factors that affect contract choice. This is accomplished using a binomial logistic regression model with data from surveys distributed to nearly two thousand tenants in the Kansas Farm Management Association database and their landlords. While there were a few noticeable trends in the data, all tenant-landowner relationships and situations are unique. Because of this, individual factors cannot be said to be definitive predictors for a particular choice of contract. Results showed that the most influential factors for a tenant were whether or not the leased land was being used to grow hay crops, whether or not the leased land was irrigated, and the tenant’s annual household income. For landowners, the most notable factors of contract choice were found to be the number of tenants a landowner worked with, whether or not the tenant was family, the risk preference of the landowner, and the age of the landowner. These variables either fall into the category of transaction cost theory or risk sharing. Arguments have been made for both theories, and the results of this study lead to the conclusion that both transaction cost and risk sharing are viable theories with a noticeable impact on contract choice.
Keywords: Lease Contract Choice